2010
DOI: 10.1111/j.1349-7006.2009.01418.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of GSTP1 I105V polymorphism on cumulative neuropathy and outcome of FOLFOX‐4 treatment in Asian patients with colorectal carcinoma

Abstract: Glutathione S-transferase P1 (GSTP1) participates in detoxification of potentially genotoxic compounds that may alter the efficacy and toxicity of platinum-based chemotherapy. We analyzed the influence of I105V polymorphism of GSTP1 on clinico-pathological features and outcomes in 166 Chinese patients with metastatic colorectal carcinoma who had been treated with first-line FOLFOX-4. Combined analysis of GSTP1 I105V, ERCC1-118, and XPD-751 polymorphisms was also conducted. The results showed that, in compariso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
60
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(66 citation statements)
references
References 33 publications
4
60
0
2
Order By: Relevance
“…By contrast, one article consisted of two independent studies, and studies included in this article were treated as separate studies (MartinezBalibrea et al, 2008). As a result, a total of 2286 CRC patients were enrolled in the 17 studies included in the pool analysis (Park et al, 2001;Stoehlmacher et al, 2004;Le Morvan et al, 2007;Ruzzo et al, 2007;Martinez-Balibrea et al, 2008;Pare et al, 2008;Lai et al, 2009;Boige et al, 2010;Chen et al, 2010;Etienne-Grimaldi et al, 2010;Farina Sarasqueta et al, 2011;Lamas et al, 2011;Chen et al, 2012;Gan et al, 2012;Li et al, 2012;Kumamoto et al, 2013). The selection procedure is shown in Figure 1, and the key patient characteristics are listed by study in Table 1.…”
Section: Search Results and Study Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…By contrast, one article consisted of two independent studies, and studies included in this article were treated as separate studies (MartinezBalibrea et al, 2008). As a result, a total of 2286 CRC patients were enrolled in the 17 studies included in the pool analysis (Park et al, 2001;Stoehlmacher et al, 2004;Le Morvan et al, 2007;Ruzzo et al, 2007;Martinez-Balibrea et al, 2008;Pare et al, 2008;Lai et al, 2009;Boige et al, 2010;Chen et al, 2010;Etienne-Grimaldi et al, 2010;Farina Sarasqueta et al, 2011;Lamas et al, 2011;Chen et al, 2012;Gan et al, 2012;Li et al, 2012;Kumamoto et al, 2013). The selection procedure is shown in Figure 1, and the key patient characteristics are listed by study in Table 1.…”
Section: Search Results and Study Selectionmentioning
confidence: 99%
“…Several studies have indicated that patients carrying the 751Gln allele tend to have a worse clinical outcome to oxaliplatin-based chemotherapy than those carrying the wild type 751Lys allele (Park et al, 2001;Le Morvan et al, 2007;Pare et al, 2008;Lai et al, 2009;Chen et al, 2010;Leichman et al, 2011). However, the opposite association was identified by two separate studies (Gan et al, 2012;Li et al, 2012), and three studies failed to provide evidence of any correlation (Martinez-Balibrea et al, 2008;Lamas et al, 2011;Kumamoto et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Their success in the treatment of cancer patients is most likely due to inducing DNA adducts, leading to the death of tumour cells [21]. DNA repair and drug metabolism have been reported to worsen the prognosis of patients receiving platinum-based chemotherapy [22,23]. Numerous studies have assessed the roles of gene polymorphisms with regard to the response to treatment and survival of different cancers, including ovarian cancer [24,25,26,27,28,29].…”
Section: Discussionmentioning
confidence: 99%
“…However, DNA repair and drug metabolism may hinder the prognosis of patients that are administered platinum-based chemotherapy (22,23).…”
Section: Discussionmentioning
confidence: 99%